CLINICAL AND PARACLINICAL CHARACTERISTICS OF PATIENTS WITH NON-FUNCTIONING KIDNEYS CAUSED BY SELECTED BENIGN DISEASES UNDERGOING SURGICAL TREATMENT AT THANH HOA PROVINCIAL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics of patients with non-functioning kidneys caused by selected benign diseases who underwent surgical treatment.Subjects and methods: A descriptive study with retrospective and prospective data collection was conducted on 73 patients diagnosed with non-functioning kidneys caused by benign obstructive diseases and surgically treated at Thanh Hoa provincial General Hospital from January 2022 to June 2025.Results: The mean age was 61.1 ± 13.9 years, and 63% of patients were older than 60 years. Chronic flank pain was the most common reason for admission (82.2%), and renal angle tenderness was found in 90.4%. Leukocytosis was present in 38.4%; positive hematuria and pyuria were observed in approximately 65.8% and 53.4%, respectively. On computed tomography, grade III-IV hydronephrosis accounted for 83.6%; renal stones 58.9%; ureteral stones 64.4%; and ureteral dilatation 71.2%. Forty-three patients (58.9%) had split renal function < 10% on radionuclide renography, while the remaining 30 cases were diagnosed on the basis of combined clinical, imaging, and post-drainage findings. All postoperative histopathology specimens were benign.Conclusions: Surgically treated patients with benign disease-related non-functioning kidneys were predominantly older adults and commonly presented with chronic flank pain (82.2%) and features of urinary obstruction/infection (83,6% grade III-IV hydronephrosis on CT scan). Computed tomography and radionuclide renography played important roles in confirming severe structural and functional renal damage and supporting surgical indication.
Keywords: Non-functioning kidney, benign disease, obstructive uropathy, nephrectomy, clinical and paraclinical features.